Integrasi Model UTAUT dan Trust terhadap Intention Digital Payment pada Mahasiswa dengan Perceived Value sebagai Variabel Mediasi - Riakbar, Bima; Malini, Helma; Hendri, M. Irfani; Wendy; Syahputri, Anggraini (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Digital transformation has driven major changes in payment systems. Although Bank Indonesia has implemented QRIS since 2019, its adoption is still hampered by the dominance of cash transactions, low user trust, and limited digital literacy. This study aims to analyze the influence of performance expectancy, effort expectancy, social influence, facilitating conditions, and trust on the intention to use QRIS with perceived value as a mediating variable. A quantitative approach was used through an online survey of 200 students in Indonesia, and the data were analyzed using the PLS-SEM method with SmartPLS. The results show that performance expectancy, effort expectancy, social influence, trust, and perceived value have a positive and significant effect on the intention to use QRIS. Conversely, facilitating conditions do not have a significant direct effect on the intention to use, but have a significant effect through the mediation of perceived value. These findings indicate that perceived value is the main mechanism that bridges technological, social, and psychological factors in shaping the intention to use QRIS. This study contributes theoretically by expanding the UTAUT model and provides practical implications for regulators and digital payment service providers to increase the perceived value of users to encourage the adoption of QRIS.